Repeat pneumococcal polysaccharide vaccine in Indigenous Australian adults is associated with decreased immune responsiveness. Issue 22 (19th May 2017) - Moberley, Sarah; Licciardi, Paul V.; Balloch, Anne; Andrews, Ross; Leach, Amanda J.; Kirkwood, Marie; Binks, Paula; Mulholland, Kim; Carapetis, Jonathan; Tang, Mimi L.K.; Skull, Sue
Abstract: Background: Indigenous adults residing in the Northern Territory of Australia experience elevated rates of invasive pneumococcal disease despite the routine use of 23-valent pneumococcal polysaccharide vaccine (23vPPV). We hypothesised that the limited protection from 23vPPV may be due to hyporesponsiveness as a result of vaccine failure from repeated vaccination. To explore this possibility, we evaluated the immune response to a first and second dose of 23vPPV in Indigenous adults and a first dose of 23vPPV in non-Indigenous adults. Methods: Serotype-specific IgG was measured by ELISA for all 23 vaccine serotypes at baseline and at one month post-vaccination. Individuals were considered to have an adequate immune response if paired sera demonstrated either: a four-fold rise in antibody concentration; a two-fold rise if the post vaccination antibody was >1.3 μg/ml but <4.0 μg/ml; or a post-vaccination antibody concentration >4.0 μg/ml for at least half of the serotypes tested (12/23). Our per-protocol analysis included the comparison of outcomes for three groups: Indigenous adults receiving a second 23vPPV dose (N = 20) and Indigenous (N = 60) and non-Indigenous adults (N = 25) receiving their first 23vPPV dose. Results: All non-Indigenous adults receiving a first dose of 23vPPV mounted an adequate immune response (25/25). There was no significant difference in the proportion of individuals with an adequate response using our definition (primary endpoint), with 88% of Indigenous adults mounted an adequate response following first dose 23vPPV (53/60) compared to 70% having an adequate response following a second dose of 23vPPV (14/20; p = 0.05). The risk difference between Indigenous participants receiving first dose compared to non-Indigenous participants receiving first dose was significant when comparing a response threshold of at least 70% (−27%, 95% CI: −43% to −11%; p = 0.01) and 90% (−38%, 95% CI: −60% to −16%; p = 0.006) of serotypes with a positive response. Conclusion: Indigenous participants demonstrated a poorer response to a first dose 23vPPV compared to their non-Indigenous counterparts, with lower IgG following a second 23vPPV dose. These findings highlight the critical need to evaluate the efficacy of future pneumococcal vaccine programs in the Australian Indigenous populations that recommend repeated doses of 23vPPV.